Treatment responsive reversible cerebral vasoconstriction syndrome with features of psychosis and large intracerebral haemorrhage. Issue 5 (8th May 2017) - Dowland, Francesca; Swayne, Andrew; Bhuta, Sandeep; Bailey, Peter; Sabet, Arman
Abstract : Objectives: To review a case of reversible cerebral vasoconstriction syndrome (RCVS) seen at a tertiary neurology centre with atypical features and rapid response to treatment. Case: A 47 year old female initially presented to the emergency department with severe sudden onset headache. Initial investigations did not reveal a cause for her presentation. Five days later she represented with a recurrence of severe headache. This was accompanied by left sided paraplegia and paraesthesia. CT revealed a large intracerebral haemorrhage with intraventricular and subarachnoid extension. Over subsequent days she worsened in her mental state, displaying features of psychosis. Further investigation did not clearly establish the underlying aetiology. Treatment was commenced with both high dose steroids and calcium channel blockade with significant, rapid improvement in the patient's mental status. Conclusions: RCVS is an increasingly well recognised condition that has the potential for significant morbidity and mortality. This case presents a unique variation in presenting features, as psychosis associated with RCVS has not been well reported in the literature. While cerebral vasculitis was a consideration for her presentation, the rapidity with which she responded to treatment does not correlate with the expected course for this diagnosis. Thus the conclusion was drawn that this patient had an atypical presentation of RCVS with associated features of psychosis.